HUBUNGAN POLA ASUH ORANG TUA DENGAN PERKEMBANGAN KECERDASAN EMOSI ANAK USIA PRASEKOLAH DI TK PANTI PURUHITA KRAPYAK KOTA SEMARANG - T.S. Widyaningsih Widyaningsih (Jurnal Ilmu dan Teknologi Kesehatan, 2016)
Based on the preliminery study analysis with 6 children, children who have a democratic parenting is 3, authoritarian is 2, and permissive is 1, so that the parenting of the children there are able to control emotions and some are spoiled on his parents. This study aimed to determine the relationship of parenting parents with emotional intelligence development of preschool children in the TK Panti Puruhita Krapyak Semarang. This study is a non-experimental, analytic survey design used cross sectional approach. The population were students in TK Panti Puruhita totaling 90 students. Sampling method used with a purposive sampling technique. Obtained 72 respondents. Instruments used are questionnairs and observation sheets. Analysis of the data using the Fisher Exact test. Based on the analysis of data obtained from 72 respondents, older people with democratic parenting were 38 (52.8%), authoritarian 30 (41.7%),permissive 4 (5.6%). Children with normal development of emotional intelligence 67 (93.1%), suspect 5 (6.9%), unstable 0 (0%). From the analysis of p value of0,001(<0.05). There is a correlation patterns of parenting with emotional intelligence development preschool children in the TK Panti Puruhita Krapyak Semarang.